Student-Centered Method in the Higher Education System of the Kurdistan Region: Soran University as an Example - Saied Qadir Faqe Ibrahim; Shamal Abdullah Abdullah (Fakultas keguruan dan Ilmu Pendidikan Universitas Muhammadiyah Kendari, 2024)
This study examines the implementation of student-centered learning at Soran University in the Kurdistan Region and identifies factors that limit its adoption. The research emphasizes student involvement in the learning process, shifting the primary responsibility from teachers to students, and assessing the approach's effectiveness. Grounded in John Dewey's "Learning by Doing" theory, which advocates for learning through activities with active student participation, the study provides a theoretical framework aligned with creating a more participatory learning environment. A structured survey was conducted with 104 teachers from various faculties and departments, focusing on the extent of student-centered practices, faculty attitudes, and organizational constraints. Data analysis through SPSS revealed a moderate adoption of student-centered approaches. However, significant barriers persist, including the continued reliance on traditional teaching methods, large class sizes, limited resources, and insufficient institutional support. These obstacles highlight the challenges educators face in fully embracing student-centered learning. The study notes some progress in implementing student-centered approaches but underscores the need for effective strategies to enhance this implementation at Soran University. Recommendations include providing more faculty training, improving resource allocation, and increasing institutional support to overcome these barriers and maximize the benefits of student-centered learning in higher education.